Femur or phalange bones as indicators of dietary phosphorus deficiency - J Hsu; G L Allee; B A Koch (Kansas Agricultural Experiment Station Research Reports, 1976)
Fifteen crossbred gilts averaging 115 pounds were fed one of three phosphorus levels 70 days (to 219 pounds average) then their femur and phalange bones were compared. Each group of five gilts had received either 0.40%, 0.50% or 0.60% total dietary phosphorus and 0.65% dietary calcium during the 70-day feeding period. The basal sorghum-soybean meal ration contained 0.30% of plant phosphorus. Specific gravity and X-ray or chemical analysis of femurs showed no significant differences among groups, but the breaking strength of femurs from gilts fed 0.6% phosphorus was significantly higher than that from gilts fed 0.4% phosphorus. Femur and phalange comparisons were inconclusive.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Femor or phalange bone; Dietary phosphorus deficiency; Calcium